Peran Karang Taruna Mencegah Politik Uang dalam Pilkades di Desa Mentoro Tahun 2020 - Tiara Fadilla Sari Dila; Sakir; Fairuz Arta Abhipraya (Departemen Ilmu Pemerintahan Fisip Unhas, 2022)
This article describes the prevention of youth organizations from using money politics in the Pilkades. Karang Taruna is a village organization for the development of the younger generation and is responsible by and for the community. With the role of this youth organization, it can accommodate the development of the younger generation who are ready and committed to supporting the implementation of the 2020 Village Head Election (Pilkades) which is clean, peaceful, safe, conducive and without syariah issues. Not only that, the youth organization also stated to prevent money politics in the election. Money politics is a hereditary culture in every concretization in Indonesia in democracy. Especially in rural areas, residents in the village are the goal in carrying out money politics. In this case, the researcher uses a qualitative method with interviewing techniques with the head of the youth organization as primary data, on the other hand, secondary data is in the form of journal articles, news, books and other library studies related to this research. The results of this study indicate that the role of youth groups in social movements is packaged in the form of socialization, successful socialization and education in preventing money politics during the Pilkades and the obstacles faced. As members of this youth organization invite community participants to work hand in hand in preventing money politics in elections.